IMPROVING CREATIVE THINKING SKILLS OF STUDENTS THROUGH LEARNING BASED ON SIMPLE HYDROPONIC PROJECTS - Nur Umami Rosidah; Herawati Susilo; Susriyati Mahanal (Universitas Negeri Malang, 2019)
Abstract: Project Based Learning (PjBL) teaches many important strategies to train various life skills to face the challenges of 21st century life, one of which is creative thinking. This quasi experiment research aims to determine the effect of project-based learning on the material of growth and development in high school students by using simple hydroponic cultivation techniques on students' creative thinking skills. The research instrument was in the form of pre test and post test questions given to the experimental class and the control class. Data analysis with independent t-test shows the results of p value < α (α = 0.05), which proves that the research hypothesis is accepted, so it can be concluded that simple hydroponic project-based learning can improve students' creative thinking skills. Key Words: PjBL, creative thinking skills, hydroponic Abstrak: Project Based Learning (PjBL) merupakan metode pembelajaran yang mengajarkan banyak strategi penting untuk melatihkan berbagai kecakapan hidup untuk menghadapi tantangan hidup abad 21, salah satunya yaitu creative thinking. Penelitian quasi experiment ini dilaksanakan dengan tujuan untuk mengatahui pengaruh pembelajaran berbasis proyek pada materi pertumbuhan dan perkembangan pada siswa SMA dengan menggunakan teknik bertanam hidroponik sederhana terhadap keterampilan berpikir kreatif siswa. Instrumen penelitian berupa soal pre test dan post test yang diberikan kepada kelas eksperimen dan kelas kontrol. Analisis data dengan independent t-test menunjukkan hasil p value < α (α = 0,05), yang membuktikan hipotesis penelitian diterima, sehingga disimpulkan bahwa pembelajaran berbasis proyek hidroponik sederhana dapat meningkatkan keterampilan berpikir kreatif siswa. Kata kunci: PjBL, keterampilan berpikir kreatif, hidroponik